Barking dogs seldom bite? a case of diagnostic overshadowing in emergency department. (13th April 2021) - Cerejeira, J. Gonçalves; Burón, C.; Carrasco, I. Santos; Meseguer, C. Capella; Vázquez, E. Rodríguez; De Llano De La Viuda, M. Queipo; Ramírez, A. Gonzaga; Valera, G. Guerra
Abstract : Introduction: Diagnostic overshadowing is one of the main consequences of stigma involving patients diagnosed with a psychiatric disorder. Some studies show that in emergency departments, being diagnosed with a psychiatric illness can lead to a poor evaluation of organic symptoms, delaying the diagnosis and putting the patient's life at risk. Objectives: - To present the case of a patient diagnosed with factitious disorder who was misdiagnosed after attending the emergency department due to the stigma related to his psychiatric diagnosis. - To provide a reflection on stigma in mental health. Methods: We will present a case report and a literature review. Results: We report a case of a 57-year-old man diagnosed with a factitious disorder. He attended the emergency department of our tertiary care center with confused speech, desorientation and disruptive behavior at home. Although the clinical picture was compatible with a confusional state, he was ordered to be admitted to the psychiatric service. No blood test was previously requested. Three hours after being admitted, he suffered an episode of seizures. A blood test was requested and severe hypomagnesemia (0.2 mg / dl) was found. Because of this episode the patient was admitted to the Intensive Care Unit for three days. Conclusions: Factitious disorder is a serious mental disorder with a significant stigmatizing burden. Giving a patient this diagnostic label should be the subject of careful thought in order to protect him from future diagnostic neglect. Disclosure: No significant relationships.